Aquabis[N′-(1,3-dithiolan-2-ylidene)-2-hydroxybenzohydrazidato(0.5−)-κ(2) N′,O]sodium(I) - Bouchameni, Chahra (International Union of Crystallography, 2012)
The title compound, [Na(C(10)H(9.5)N(2)O(2)S(2))(2)(H(2)O)], is a molecular sodium complex with N′-(1,3-dithiolan-2-yl)-2-hydroxybenzohydrazide ligands with the negative charge spread evenly over both, and a water molecule. The Na(I) ion coordination is distorted trigonal–bipyramidal, formed by two N and three O atoms, with the Na(I) ion lying on a twofold rotation axis. Intramolecular N—H⋯O hydrogen bonds occur. Molecules pack as discrete units and the crystal packing is stabilized by strong O—H⋯O hydrogen bonds, which give rise to chains along [010]; the chains are interlinked by strong O—H⋯O hydrogen bonds.